The three Cs of democracy promotion policy: context, consistency and credibility - Jörn Grävingholt; Julia Leininger; Oliver Schlumberger (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Democracy's march to presumed global victory has ground to a halt. Democracy promotion, a boom industry in the 1990s, has come under criticism. While there are still good reasons to promote democracy abroad, there must be some rethinking if new successes are to be achieved: moving away from unconnected measures in support of individual elements of democracy towards a context-specific, consistent and credible long-term policy of democracy promotion.
Keywords: 330